PRODUCT INNOVATION OF SMEs IN VUCA ERA - Muhammad Danial, R. Deni; Alhidayatullah, Alhidayatullah; Khairul Amal, Muhammad; Abdul Aziz, Muh. (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This paper examines SMEs product innovation in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. One of the common problems for SMEs in Indonesia is challenges related to product innovation. These challenges are limited human resources and lack of access to technology and knowledge. Thus, product innovation will continue to develop not only with a touch of technology orientation, but also requires optimal inter-functional coordination. This study used quantitative methods on 205 SMEs as respondents. There are three variables that are the object of study, they are Product Innovation as the dependent variable, Technology Orientation as the independent variable and Inter-Functional Coordination as the mediating variable. The results of this study state that the Inter-Functional Coordination variable mediates the relationship between the Technology Orientation variable and the Product Innovation variable. Thus, Technology Orientation will not be optimal in developing SMES Product Innovation, unless SMESs strengthen Inter-Functional Coordination. Inter-functional coordination is a process where various functions or departments in an organization work together and collaborate to achieve common goals.